2009
DOI: 10.1262/jrd.09-069a
|View full text |Cite
|
Sign up to set email alerts
|

Expression of c-MYC in Nuclear Speckles During Mouse Oocyte Growth and Preimplantation Development

Abstract: Abstract. Myelocytomatosis oncogene (c-myc) is a major transcriptional regulator that controls various biological processes, and its deregulated expression causes carcinogenesis. To investigate the involvement of c-myc in oogenesis and preimplantation development, the expression of c-MYC during these stages was examined by immunocytochemistry. A strong c-MYC signal was detected in the nucleus of growing and fully grown oocytes as well as in preimplantation embryos before the morula stage. The signal intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…In these oocytes, however, RPB1 was not bound to DNA; it was not detected in the nucleus when the oocytes were fixed in the presence of Triton X-100. Next, we treated growing oocytes with DRB, which inhibits RPB1 phosphorylation and can condense the chromatin in oocytes and somatic cells [19,20]. The DRB treatment condensed the chromatin and changed its configuration to an SNtype pattern.…”
Section: Involvement Of Chromatin Condensation In the Dissociation Ofmentioning
confidence: 99%
“…In these oocytes, however, RPB1 was not bound to DNA; it was not detected in the nucleus when the oocytes were fixed in the presence of Triton X-100. Next, we treated growing oocytes with DRB, which inhibits RPB1 phosphorylation and can condense the chromatin in oocytes and somatic cells [19,20]. The DRB treatment condensed the chromatin and changed its configuration to an SNtype pattern.…”
Section: Involvement Of Chromatin Condensation In the Dissociation Ofmentioning
confidence: 99%
“…These gene expression profiles may have been caused by demethylation of H3K27 during the blastocyst stage. However, no c-Myc signal was detected in blastocysts (Suzuki et al, 2009). A previous study reported that the Ezh2 protein was observed in ICM cells according to immunofluorescence results (Zhang et al, 2009), indicating that Ezh2 and development-related genes are co-localized in mouse blastocysts.…”
Section: Discussionmentioning
confidence: 80%
“…Oct4, Sox2, Nanog, Klf-4, and c-Myc correlated with the development potential of preimplantation embryos, the maintenance of ES cell pluripotency, and iPS cell totipotency (Li et al, 2005;Takahashi and Yamanaka, 2006;Suzuki et al, 2009). Oct4, Sox2, Nanog, and Klf-4 proteins were observed to be in the ICM cells of blastocysts; the fluorescence intensity increased with embryonic development, peaking during the blastocyst stage (Rodda et al, 2005;Zhang et al, 2009;Keramari et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Three of Yamanaka factors were found in the ooplasm of mouse-matured oocytes, including Oct4, Sox2, and c-Myc (Palmieri et al 1994;Avilion et al 2003;Suzuki et al 2009). Yamanaka factors existed in ESCs, and as mentioned above, ectopic expression of these factors could reprogram several types of mammalian somatic cells into iPSCs.…”
Section: Matured Oocytes Were Endowed With Totipotent Developmental Pmentioning
confidence: 99%